UPAYA GURU BIMBINGAN KONSELING DALAM MENINGKATKAN SELF-ESTEEM SISWA DI MTsN 4 ACEH BESAR - Muhammaad Nazar; Wanty Khaira (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine in depth the efforts of Guidance and Counseling teachers in enhancing students' self-esteem at MTsN 4 Aceh Besar. Self-esteem is a crucial aspect of students’ psychological development, significantly influencing their self-confidence, learning motivation, and social interaction. The study employs a descriptive qualitative approach, with data collected through in-depth interviews and direct observation. The findings show that Guidance and Counseling teachers implement various personal and responsive strategies, such as individual counseling, group counseling, monitoring student development, and collaborating intensively with homeroom teachers and parents. These strategies are tailored to the characteristics and needs of students with low self-esteem. Teachers also create a supportive environment and provide positive reinforcement to help boost students' self-esteem. The challenges faced include students’ reluctance to open up, limited counseling facilities, and lack of parental involvement. Nevertheless, the interventions carried out have proven to positively impact the improvement of students' self-esteem, particularly in aspects of social interaction, confidence in self-expression, and engagement in learning processes. This study emphasizes the importance of a holistic and collaborative approach in school-based counseling services to support students' psychological well-being and optimal personal development